Removal of lithium, sodium, and phosphate from the Li-ion battery cathode recycling process using column adsorption - Nurkhopipah, Siti (Universitas Wiralodra, 2023)
Lithium Ion Battery (LIB) is one type of battery whose demand is increasing every year. After the Li-ion battery usage cycle ends, more and more waste is generated. Wastewater from the LFP battery cathode recycling process still contains metals such as lithium, sodium, and phosphate. This experiment was carried out using the adsorption method. The adsorption method is used to remove metal ions in LFP battery waste. The adsorption process took place in a semi-continuous fixed-bed column made of glass cylinders with a height of 50 cm and a diameter of 2.5 cm. The artificial waste solution flowed into a column containing 135 g of activated carbon with variations in flow rates of 10, 15, and 20 mL/min for 2 hours. The concentration of the initial solution and the filtrate was analyzed using an Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES). The experimental results showed that the maximum percentage removal of lithium, sodium, and phosphate at a flow rate of 10 mL/min was 95.22%, 96.42%, and 68.02%, respectively. In addition, the results of the adsorption kinetic studies reviewed using the Thomas and Yoon-Nelson models showed that the column adsorption performance for lithium, sodium, and phosphate was most effective at a flow rate of 10 mL/min with an adsorption capacity of 8.75.105 mg/g, 8.85.105 mg/g, and 3.91.105 mg/g, respectively. Meanwhile, the breakthrough times for lithium, sodium, and phosphate were 335 minutes, 441 minutes, and 126 minutes, respectively.